Risk attitudes with state-dependent indivisibilities in consumption - Markus Fels (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
Some consumption opportunities are both indivisible and only valuable in particular tates of nature. The existence of such state-dependent indivisible consumption opportunities influences a person's risk attitudes. In general, people are not risk averse anymore even if utility from divisible consumption is concave. I propose a definition of insurance in the context of state-dependent preferences and investigate the different motives underlying insurance demand. The same reasons that rule out risk aversion turn out to be the basis of a desire to insure. This calls into question the standard approach that bases insurance demand on risk aversion with important implications for policy and research. – – Einige Konsummöglichkeiten sind nicht teilbar und nur in bestimmten Naturzuständen wertvoll. Die Existenz solcher zustandsabhängigen, unteilbaren Konsummöglichkeiten beeinflusst das Risikoverhalten einer Person. Im Allgemeinen sind die Menschen nicht mehr risikoscheu, auch wenn der Nutzen aus dem teilbaren Konsum konkav ist. Ich schlage eine Definition von Versicherung im Zusammenhang mit zustandsabhängigen Präferenzen vor und untersuche die verschiedenen Motive für Versicherungsnachfrage. Die gleichen Gründe, die Risikoaversion ausschließen, erweisen sich als Grundlage für den Wunsch nach einer Versicherung. Damit wird der Standardansatz in Frage gestellt, nach dem Versicherungsnachfrage auf Risikoaversion beruht, mit wichtigen Konsequenzen für Politik und Forschung.
Keywords: D01; D81; 330; risk preferences; indivisible consumption; insurance; gambling